Interpersonal Relations of a School Counsellor - Zierkiewicz, Edyta (INSTED: Interdisciplinary Studies in Education & Society, 1998)
Being one of the elements of school system, the school counsellor is involved in numerous interpersonal contacts taking place at the area of the school. The social groups that the school counsellor is in touch with are first of all students, their parents, teachers and the school heads. Depending on the preferred values and motivations the school counsellor chooses a reference group, and tries to fulfil and cater for their expectations and needs.